2018
DOI: 10.22271/ortho.2018.v4.i3a.03
|View full text |Cite
|
Sign up to set email alerts
|

Choice of implant in stable intertrochanteric fracture femur: PFNA vs DHS

Abstract: Introduction:The best treatment for trochanteric fracture remains controversial Many methods have been recommended. Stable fixation that allows early mobilization is the treatment of choice. In this study, we aimed to compare the results of osteosynthesis using the PFNA and DHS system, in the treatment of stable intertrochanteric fractures including operative and postoperative complications, general complications and final outcome measurements. Method: We randomised 60 patients with low-energy extracapsular pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This could imply that the high observed failure rate compared to these previous studies has resulted from a discrepancy in what was classified as an implant failure. The definitions of the other studies, compared to the one of this study, seems either too vague to be sure [1,4,20], or seems to match reasonably [5,31]. Other potential reasons for the significant discrepancy in the failure rates, such as differences in the patient populations, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…This could imply that the high observed failure rate compared to these previous studies has resulted from a discrepancy in what was classified as an implant failure. The definitions of the other studies, compared to the one of this study, seems either too vague to be sure [1,4,20], or seems to match reasonably [5,31]. Other potential reasons for the significant discrepancy in the failure rates, such as differences in the patient populations, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 75%
“…Only Yu et al presented failure rates in the order of magnitude observed in our cohort [1,4,5,20,31]. While Adams et al (2001) reported only failures which were reoperated, some studies stated less clearly whether non-reoperated failures were also included as implant failures [4,20]. Only Cho et al (2016) and clearly included these non-reoperated failures also [5,31].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations